AudioMove – lyddramatik i bevægelse - Bitsch D’Souza, Mette Marie (Peripeti, 2015)
The article centers on Teater Katapult’s AudioMove concept and examines the potential for bodily engagement and multi-sensory experiencing that the concept provides via the site-specific experience and positioning of the spectator.